2012
DOI: 10.1002/art.33446
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐22 promotes osteoclastogenesis in rheumatoid arthritis through induction of RANKL in human synovial fibroblasts

Abstract: Objective. To examine the regulatory role of interleukin-22 (IL-22) in the expression of RANKL and induction of osteoclastogenesis in rheumatoid arthritis (RA).Methods. Concentrations of IL-22 and RANKL in the serum and synovial fluid of RA patients were measured using enzyme-linked immunosorbent assay. RA synovial fibroblasts were treated with recombinant human IL-22 (rhIL-22), and the expression of RANKL messenger RNA (mRNA) and protein was measured using real-time polymerase chain reaction, Western blotting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
119
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 60 publications
10
119
1
2
Order By: Relevance
“…The IL-22 concentration in synovial fluid was higher in patients with RA compared with controls 2,3 . In patients with RA, Th17 cells were recognized to produce higher IL-22 4 .…”
Section: To the Editormentioning
confidence: 78%
“…The IL-22 concentration in synovial fluid was higher in patients with RA compared with controls 2,3 . In patients with RA, Th17 cells were recognized to produce higher IL-22 4 .…”
Section: To the Editormentioning
confidence: 78%
“…Besides its proinflammatory effects in autoimmune diseases and host defense, IL-17 can recruit neutrophils into the airways in allergic asthma [38]. After IL-22 was first described [39], extensive studies have shown that IL-22 has immunological effects, predominantly proinflammatory, in various diseases or models, such as bleomycin induced lung inflammation, and other disease models, including arthritis, hepatitis, psoriasis, atopic dermatitis, and inflammatory bowel disease [11,[40][41][42][43][44][45]. In the lung, IL-22 plays a key role in controlling bacteremia in experimental gram-negative pneumonia and airway tissue repair after influenza infection [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 also increases the production of vascular endothelial growth factor (VEGF) in rheumatoid ibroblast-like synoviocytes (FLS), contributing to the angiogenesis in rheumatoid synovium. Finally, IL-17 stimulates the expression of various pro-inlammatory cytokines (e.g., IL-1β, TNF-α, and IL-6) and matrix-degrading enzymes (e.g., matrix metalloproteinase (MMP)-1, matrix metalloproteinase-2, matrix metalloproteinase-9, and matrix metalloproteinase-13) in whole synovial tissue, synovial ibroblasts, and cartilage, thus promoting inlammation, extracellular matrix breakdown, and cartilage destruction during RA development [61][62][63][64][65].…”
Section: Altered Gut Microbiota and Inlammation In Rheumatoid Arthritismentioning
confidence: 99%